THE SELF-DISCLOSURE VICTIMS OF ONLINE GENDER-BASED VIOLENCE ON TWITTER SOCIAL MEDIA - Sania, I Luh Devi; Arianto; Farid, Muhammad (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2023)
Online gender-based violence (GBV) is a form of violence that has the intention or meaning of harassing victims based on gender or sexual activity online or the use of internet technology. The objective study is to analyze reasons why victims of Online gender-based violence (GBV) choose to do self-disclosure on Twitter compared to other social media or directly disclose themselves. Result of the study shows that encouragement for online GBV victims to disclose themselves on social media Twitter is more comfortable with features such as Twitter's anonymity and speed, which make some topics popular. Social media such as Instagram, Facebook, TikTok, drip emphasize visual and audio-visual content that makes victims uncomfortable enough to self-disclose with content like That. The second is what the victims revealed about themselves as a form of concern against others on Twitter who can become online GBV victims. Third, online GBV victims need a place and encouragement from other victims who have revealed themselves on social media, so disclosure on Twitter can motivate other victims to reveal themselves bravely. Keywords: Self Disclosure, Online GBV Victims, Twitter.